Mutational status of TP53 defines the efficacy of Wee1 inhibitor AZD1775 in KRAS-mutant non-small cell lung cancer - Ku, Bo Mi (Oncotarget, 2017)
KRAS is frequently mutated in non-small cell lung cancer (NSCLC). However, direct targeting of KRAS has proven to be challenging, and inhibition of KRAS effectors has resulted in limited clinical efficacy. Wee1 kinase is an important regulator of the G2 checkpoint and is overexpressed in various cancers. Inhibition of Wee1 exerts anticancer effects as a monotherapy or in combination with DNA-damaging agents when cancer cells harbor TP53 mutations. However, its role in KRAS-mutant NSCLC, especially as a single agent, has not been explored. Here, we investigate the anticancer potential of Wee1 inhibitor AZD1775 as a monotherapy and uncover a possible cellular context underlying sensitivity to AZD1775. Our data show that treatment with AZD1775 significantly inhibited cell survival, growth, and proliferation of TP53-mutant (TP53(MUT)) compared to TP53 wild-type (TP53(WT)) in KRAS-mutant (KRAS(MUT)) NSCLC cells. In KRAS(MUT)/TP53(MUT) cells, AZD1775 treatment led to DNA damage, a decrease of survival signaling, and cell death by apoptosis. Interestingly, cell death through apoptosis was found to be heavily dependent on specific cellular genetic context, rather than inhibition of Wee1 kinase activity alone. In addition, AZD1775 treatment was well tolerated and displayed single-agent efficacy in a mouse xenograft model. This study provides rationale for inhibiting Wee1 using AZD1775 as a potential anticancer therapy against the TP53(MUT) subgroup of KRAS(MUT) NSCLC.